LAW ENFORCEMENT AGAINST THE CRIME OF COUNTERFEITING HERBAL MEDICINE (STUDY AT THE NORTH SUMATRA POLICE) - Frikson Try Haryadi Hutasoit; M. Citra Ramadhan; Andi Hakim (SOSIOEDUKASI, 2026)
This thesis research is entitled Law Enforcement Against Criminal Acts of Herbal Medicine Counterfeiting (Study of North Sumatra Regional Police). The formulation of the problem is: What are the legal regulations for herbal medicine counterfeiting in legislation? What factors cause the occurrence of criminal acts of herbal medicine counterfeiting? How is law enforcement carried out by the North Sumatra Regional Police against perpetrators of herbal medicine counterfeiting? The research method used is normative juridical legal research, with a descriptive analytical research type. For the problem approach, a normative juridical approach is used. The data used are primary and secondary data. The results of the study show that the legal regulations for herbal medicine counterfeiting are the Minister of Health Regulation No. 24 of 2018 concerning Permits and Implementation of Traditional Herbal Medicine Health Worker Practices, Law No. 17 of 2023 concerning Health, and Government Regulation No. 103 of 2014 concerning Traditional Health Services. A factor contributing to the occurrence of counterfeit herbal medicine is the lenient penalties for perpetrators of counterfeiting herbal medicine, which has led to increased activity, particularly in counterfeiting herbal medicine. The North Sumatra Regional Police's law enforcement efforts against perpetrators of counterfeit herbal medicine involve conducting investigations and inquiries until the files are received by the Prosecutor's Office for trial.